Mobile agent based mid-range electronic commerce transactions - Ong, Chee Chye. (2008)
This dissertation provides a literature survey of electronic payment systems that can be grouped into five broad classes: credit-card based systems, electronic cheque, centralized account based systems, electronic cash and micropayment systems.